2017
DOI: 10.1002/aoc.3739
|View full text |Cite
|
Sign up to set email alerts
|

Water‐soluble Schiff base Cu(II) and Zn(II) complexes: Synthesis, DNA targeting ability and chemotherapeutic potential of Cu(II) complex for hepatocellular carcinoma –in vitroandin vivoapproach

Abstract: Reliable compounds with low toxicity are tempting potential chemotherapeutics. With an aim of achieving less toxic but more potent metallodrugs, four new-generation hydrophilic Cu(II) and Zn(II) complexes with DNA-targeting properties were synthesized and characterized using various physicochemical data. The excellent DNA binding and cleavage results confirmed the mode of binding of DNA with the complexes and their ability to denature it. The profound in vitro cytotoxicity exhibited by complex 3 against a pane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 53 publications
0
6
0
1
Order By: Relevance
“…We chose this cell line because it has already been established as an in vitro model for human cell cytotoxicity of antimalarials, or their formulations, by many other authors [ [77] , [78] , [79] , [80] , [81] ]. The scientific literature also provides examples of the use of fibroblasts as exemplary control lines representing healthy cells, or to demonstrate selectivity for various types of compounds or formulations [ [82] , [83] , [84] ]. As we previously demonstrated, free 3, with an IC 50 32043.3 ± 1429.5 ng/ml determined for the NHDF cell-line ( Table 1 ), has negligible effect on cell viability at the tested concentration range.…”
Section: Resultsmentioning
confidence: 99%
“…We chose this cell line because it has already been established as an in vitro model for human cell cytotoxicity of antimalarials, or their formulations, by many other authors [ [77] , [78] , [79] , [80] , [81] ]. The scientific literature also provides examples of the use of fibroblasts as exemplary control lines representing healthy cells, or to demonstrate selectivity for various types of compounds or formulations [ [82] , [83] , [84] ]. As we previously demonstrated, free 3, with an IC 50 32043.3 ± 1429.5 ng/ml determined for the NHDF cell-line ( Table 1 ), has negligible effect on cell viability at the tested concentration range.…”
Section: Resultsmentioning
confidence: 99%
“…[ 76 ] The phenyl ring of phenanthroline of complex 1 also interacts with DNA via an electrostatic interaction (anion‐π) with the phosphate group of cytosine 33 (Cyt33), which stabilises the DNA binding. [ 77,78 ] The binding energy associated with the binding of complex 1 with DNA in the energy minimised docking pose was −420.3 kcal/mol. A 1,10‐phenanthroline is a good candidate for binding with DNA base pairs due to the in‐plane distortion of phenanthroline moiety on complexation.…”
Section: Resultsmentioning
confidence: 99%
“…27,28 In the past few years, specifically after the successful discovery of cisplatin, the 3d metal complexes of different ligands including Schiff bases have been widely explored in medicine, especially in the pharmaceutical field, because of their ability to act as DNA-targeting agents. [29][30][31][32] In this respect, it has been reported that complexes containing Ni(II), Zn(II) and Cu(II) metal ions are the most suitable ones owing to their biocompatibility and bio-activity. 33 In the study of potential anti-cancer agents using Schiff base complexes, much attention has been given to exploring the interaction between the 3d metal centre and DNA in order to nullify the side effects of cisplatin.…”
Section: Introductionmentioning
confidence: 99%
“…and Tables S3, S4, S6, and S8, ESI †). The penta-coordinated (4 + 1) metal centre in 1 has an Addison distortion index29 (t) value of 0.359, suggesting a highly distorted square pyramidal geometry for the Cu(II) metal center. The penta-coordination geometry around the central metal atom in 2 can adopt either a square pyramidal or trigonal bipyramidal (TBP) geometry.…”
mentioning
confidence: 99%